Framing the sky. Thoughts on the temporary close of a skyspace of James Turrell - Martínez García-Posada, Ángel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
The news of the partial closing of the piece Meeting by James Turrell at the MoMA PS1 in New York during some months of 2019 encourages an architectural and artistic reflection on some issues of interest in the work of this artist in his Skyspaces series, specially his ideas on the notion of limit, as well as his challenge to approach the flatness of the framework from the constructive rigor of detail, the decantation of the notion of architecture as the dialogue with light, the illustration of the shapes ability to trap frames or guide the universe, and ultimately certain inquiry of an art idea that interacts with the records of space and time.
Keywords: Space; Time; Light; Frame; Limit; Art and architecture